The potential of high molecular chitosan nanohydroxyapatite as an irrigant in improving fracture resistance after root canal treatment (In Vitro) - Ertha Dini FINANTI; Trimurni ABIDIN (Journal of Syiah Kuala Dentistry Society, 2021)
ABSTRACT Teeth after root canal treatment are at a higher risk of fracture than vital teeth. After root canaltreatment, the causes of tooth fracture are multifactorial, both iatrogenic and non iatrogenic. One of them isirrigants, although very useful for disinfection. Irrigants are known to change the chemical components andstructure of the root canal surface dentin by modifying the proportion of calcium and phosphate minerals. Thisresearch is an experimental laboratory study with a post-test-only group research design to analyze the effect ofirrigating solutions of nanohydroxyapatite, high molecular chitosan, NaOCl, and EDTA with their appropriatecombination for the test group on the fracture resistance of teeth after root canal treatment. Root canal treatment wasperformed on 24 mandibular premolars, with the group I; irrigating solution of nanohydroxyapatite, group II;irrigation of nanohydroxyapatite solution with the addition of 0.2% chitosan, group III; irrigation with 2.5% NaOClsolution and 0.2% chitosan solution, group IV; irrigation solution of 2.5% NaOCl and 17% EDTA. ANOVA testshowed a significant difference in fracture resistance (p0.05) between each group. The highest average fractureresistance was seen in group II, namely the irrigation group using a solution of nanohydroxyapatite with theaddition of 0.2% chitosan, which was 363.644 10,896 N. fracture after root canal treatment.KEYWORDS: nanohydroxyapatite, irrigation solution, fracture resistance